Kebutuhan Pembaharuan Hukum Islam Sesuai Dengan Kebutuhan Zaman Kontemporer - Septian Fiktor Riyantoro (Indonesia, 2021)
The problems faced by Muslims are increasingly complex. The challenges of modern life cannot be overcome simply by citing old religious interpretations. Not only because they are irrelevant, but because old interpretations often create new problems. How much terror, violence, discrimination, and dehumanization is done by referring to religious texts. The research method used is descriptive qualitative with a phenomenological approach. Data collection by observation, interviews, and documentation. Data analysis was carried out by means of data documentation, data reduction, data display and drawing conclusions. The results of the study show that the paradigm shift in the methodology of Islamic law carried out by the figures has implications for aspects of Islamic law both methodologically and discourse. Therefore, the method of reforming Islamic law is not a method that can be separated from the renewal of thoughts that move from the sacred texts that can be understood and then carried out in the context of the modern world which of course is no longer the same as the context of the time of the prophet. So that there is an offer of renewal of contemporary Islamic law methods including Fazlur Rahman, Muhammad Syahrur.